Health literacy and its effect on chronic disease prevention: evidences from China's national health literacy surveillance data - Liu, lefan; Qian, Xujun; Chen, Zhuo; He, Tianfeng (University of Nottingham Ningbo China, 2019)
Objectives Improving health literacy is an important public health goal in many countries. Although many studies have suggested that low health literacy has adverse effects on an individual’s health outcomes, factors that may be confounding the relationship between health literacy and health outcomes are often not accounted. This paper examines the interplay between health literacy and chronic disease prevention.